The skill bias effect of technological and organisational change : evidence and policy implications - Mariacristina Piva; Enrico Santarelli; Marco Vivarelli (Institute for the Study of Labor (IZA), 2003)
Previous empirical literature has shown that technological change can be considered the main cause of the skill bias (increase in the number of highly skilled workers) exhibited by manufacturing employment in developed countries over the last decades. However, recent papers have also introduced the ?Skill Biased Organisational Change? hypothesis. We estimate a SUR model for a sample of 400 Italian manufacturing firms, showing that upskilling is more a function of the reorganisational strategy than a consequence of technological change alone. Moreover, some evidence of superadditive effects emerges, consistently with the theoretical hypothesis of a coevolution of technology and organisation.
Keywords: J50; O33; 330; skill bias; organisational change; manufacturing; Qualifikation; Arbeitsangebot; Arbeitsnachfrage; Technischer Fortschritt; Reorganisation; Organisatorischer Wandel; Schätzung; Italien